2019
DOI: 10.3390/ijerph16132391
|View full text |Cite
|
Sign up to set email alerts
|

Factors Underlying Unmet Medical Needs: A Cross-Sectional Study

Abstract: Unmet medical needs refer to the state where a patient’s medical care or service is insufficient, inadequate, or lacking. Numerous factors influence unmet medical needs. We used a multi-pronged approach to explore the factors influencing unmet medical needs in the Korean health care system according to Anderson’s Behavioral Model of Health Services Use. To this end, we used data from 11,378 adults over 19 years old in the 2016 Korea Health Panel Survey and performed multiple logistic regression analyses. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
7
16
0
Order By: Relevance
“…Similar results were obtained for variables such as age [21,26,27,36], marital status [37], [40], educational status [26,39,41] and household income [28,42].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results were obtained for variables such as age [21,26,27,36], marital status [37], [40], educational status [26,39,41] and household income [28,42].…”
Section: Discussionsupporting
confidence: 78%
“…Chronic disease groups with no signi cant difference; infarction, hypertension, stroke/paralysis, diabetes, urinary incontinence, Alzheimer's. In similar studies in the literature [37], chronic diseases have a signi cant effect on unmet health care.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As complementary health insurance might not be accessible to disadvantaged groups, policy makers need to do their utmost efforts to create inclusive basic insurance programs to tackle unmet need effectively. Previous studies [32,35] also confirmed the protective effect of health insurance against unmet need. Similar to other studies [9,11,12,14], poor health status and the larger number of needs for outpatient healthcare services were the strongest predictors of unmet need in the first and second regression models.…”
Section: Discussionsupporting
confidence: 53%
“…If the patient was not treated in a timely manner, owing to the occurrence of unmet medical care, it might increase the possibility of the patient acquiring moderate degree diseases and their accompanying complications. Since preventing unmet medical care helps to alleviate symptoms, as well as to prevent and treat diseases, it is considered a medical problem that needs to be solved [11,12]. Andersen's behavioral model is used to analyze the predictors of medical service use and how these affect patient outcomes, such as health condition and health satisfaction.…”
Section: Introductionmentioning
confidence: 99%